Flame Atomic Absorption Spectrometric Determination of Trace Quantities of Cadmium from Water Samples - Tas, Deniz Sahin (Asian Journal of Chemistry, 2017)
The influence of some surface-active agents in the medium on determination of ultra-trace quantities of Cd2+ ion by flame atomic absorption spectrometry was investigated. Sodium dodecylsulfate (SDS), cetyltrimethyl ammonium bromide (CTAB) and polyoxyethylene(10) isooctylphenyl ether (TX100) were used as anionic, cationic and non-ionic surface-active agents, respectively. To obtain the optimal concentration of surfactants, the effect of surfactant concentration on the preconcentration of cadmium was investigated by increasing sufactant concentration up to 10 × critical micellar concentration (CMC). The analytical characteristics of the method (e.g., limit of detection, linear range, preconcentration and improvement factors) were obtained. The limits of detection for cadmium are 0.7, 0.3 and 0.3 ppm in presence of SDS, CTAB and TX100, respectively. The method was applied for determination of cadmium in wastewaters.